A Odisséia Ateniense: Antônio Lopes da Cunha e a invenção de um Maranhão na Primeira República - SANTOS, Rafael Aguiar Dos (2023)
This work aims to understand historiographically the issued discourse by the intellectual Antônio Lopes da Cunha from Maranhão during the First Republic. The sources analyzed are three articles written by him and published in 1926 in the today’s first magazine Instituto Histórico e Geográfico do Maranhão (IHGM, Historical and Geographical Institute of Maranhão): Marília e Dirceu, The Historical and Geographical Dictionary of Maranhao and Armorial Maranhense; as well as his book Alcântara: subsidies for the city history. As a theoretical reference, we used concepts from Roger Chartier's New Cultural History; the French Discourse Analysis (AD) of Michel Foucault and Dominique Maingueneau; as well as Mikhail Bakhtin's Dialogic Discourse Analysis (ADD). Connecting the text, the author and its context, we weave a network about Maranhão by Antônio Lopes da Cunha in the First Republic. Through this theoretical framework, we analyze the vision of the History writing method, project of Maranhão, Local Identity and Maranhão History present in our Maranhão intellectual writing.